Animal fun - Watt, Fiona; Allman, Howard; Lovell, Katie (London : Usborne Pub, 2008)
Provides instructions for such simple craft projects featuring wild animals as a painted lion, a crocodile collage, and felt monkeys.
Keywords: Animals in art -- Juvenile literature; Handicraft -- Juvenile literature